The First Polish 'Anthropology' and its Author Józef Jasiński - Gronkiewicz, Stanisław (Anthropological Review, 1987)
This brief presentation familiarizes the reader with the onset of Polish anthropology and the role the Vilnius centre played in its development. Subsequently comes the biography of the physician, Jozef Jasiński, who wrote the first Polish book on anthropology, issued in 1818 in Vilnius. His work "Anthropology of physical and moral features of man" ("Anthropologia o własnościach człowieka fizycznych i moralnych") is comprised of three parts. In the preface he introduces an interesting definition of anthropology which is thus described as "a science of physical and moral features of man, revealing his dignity elevated above other physical beings".In the first part Jasiński sets man against his natural environment, places him in the zoological taxonomy and gives the principles of human gait. The second part shows man in his milieu and ennumerates stages of the development of economic community: 1) gathering, 2) fishing and hunting, 3) pasturing, and 4) farming. The third part deals with build and functioning of human organism, kinds of motion, build of sensory organs and differences between man and animals. Concluding, he describes the ontogenesis of man which combines seven stages, namely embryo, childhood, adolescence, maturity, adulthood, senescence, senility. This classification along with other fragments of his book is still up to date.He wrote his book when anthropology was only sprouting and it was not until the 50s of the past century that this science had flourished and first institutes had been formed.